Modified Lapidus Procedure with a Single Screw and Staple: A Comparative Analysis - Sakkab, Ramez; Liew, Victoria; Porto-Kujanpaa, Stephanie E. Dal; Diaz, Ryan M.; Collins, Michael L. (Journal of the Foot & Ankle, 2025)
Objective: The primary objective of the study is to review the fusion rate associated with a single screw and staple construct in Lapidus bunionectomy, and to compare the complication rates, fusion outcomes, and radiographic results with those of other common fixation methods. Methods: Eighty-four bunionectomies met study criteria; in 24 cases, a single screw and staple construct was used, while 28 used a screw and locking plate, and 32 used two crossing screws. Although group matching was attempted, a greater body mass index was observed in the screw and locking plate group (p = 0.006). Results: The minimum follow-up was 12 months (mean, 31.4 months), and the primary outcome was fusion rate. Union rates were achieved in 95.8% for the single screw and staple fixation (23/24), 92.8% for the screw and locking plate (26/28), and 93.8% for crossing screws (30/32) without a statistically significant difference (p = 0.474). The single screw and staple group achieved significantly (p = 0.012) earlier radiographic and clinical union, at 11.7 (+ 1.86) weeks, compared to crossing screw (13.2 + 2.39 weeks) and screw and locking plate (13.5 + 1.69 weeks) groups. There were no significant differences in final first intermetatarsal angle (p = 0.403), hallux valgus angle (p = 0.153), or complication rates (p = 0.386) among the fixation methods. Conclusion: Our study shows that a single screw and staple construct is a viable option for Lapidus bunionectomy, demonstrating faster union time and maintained deformity correction with an acceptable complication rate. However, further research is required to validate the advantages and disadvantages of specific surgical implants. Level of evidence: III, retrospective case control study